Дослідження та програмна реалізація системи мобільного контролю вантажоперевезень на базі ОС Android - Середа, Владислав Леонідович; Sereda, Vladyslav (ЦНТУ, 2023)
В даній випускній кваліфікаційній роботі за другим (магістерським) рівнем вищої освіти розроблено програмне забезпечення, яке призначено для системи мобільного контролю вантажоперевезень на базі ОС Android. Метою розробки є дослідження та програмна реалізація системи мобільного контролю вантажоперевезень на базі ОС Android. Об’єктом дослідження є процес мобільного контролю вантажоперевезень на базі ОС Android. Предметом дослідження є методи мобільного контролю вантажоперевезень на базі ОС Android. Методи дослідження базуються на методах розробки мобільних додатків, методах математичної статистики, методах розробки програмного забезпечення. Результат роботи – програмна реалізація системи мобільного контролю вантажоперевезень на базі ОС Android. В процесі роботи над програмною моделлю виконано аналіз існуючих апаратних та програмних засобів. В повній мірі описані всі компоненти розробленого програмного забезпечення. Розроблено зручний інтерфейс користувача. Наведені інструкції по роботі з програмними засобами. Програма може використовуватися на мобільному пристрої під керуванням ОС Android. Програму розроблено в середовищі Java, Eclipse, Android SDK. In this graduation thesis for the second (master's) level of higher education, software is developed, which is intended for the mobile control system of cargo transportation based on the Android OS. The goal of the development is the research and software implementation of the mobile cargo transportation control system based on the Android OS. The object of the study is the process of mobile control of cargo transportation based on the Android OS. The subject of the study is the methods of mobile control of cargo transportation based on the Android OS. Research methods are based on mobile application development methods, mathematical statistics methods, and software development methods. The result of the work is the software implementation of the mobile cargo transportation control system based on the Android OS. In the process of working on the software model, an analysis of existing hardware and software was performed. All components of the developed software are fully described. A convenient user interface has been developed. Instructions for working with software tools are provided. The program can be used on a mobile device running the Android OS. The program was developed in the environment of Java, Eclipse, Android SDK.
Research and software implementation of a mobile cargo transportation control system based on the Android OS
Keywords: комп’ютерні науки; вантажоперевезення; ОС Android; computer science; trucking; Android OS